Застосування схем апроксимації для дослідження стійкості розв’язків лінійних диференціально різницевих рівнянь - Піддубна, Лариса (Чернівецький національний університет імені Юрія Федьковича, 2022)
This paper investigates the application of approximation schemes for differential-difference equations [1-3] to construct algorithms for the approximate finding of nonsymptotic roots of quasipolynomials and their application to study the stability of solutions of systems of linear differential equations with delay.
Keywords: дослідження стійкості, схема апроксимації, лінійно диференціально-різницеві рівняння